FISH DIVERSITY IN THE DOWNSTREAM REGION OF CIPANAS RIVER INDRAMAYU, WEST JAVA INDONESIA - Titin Herawati; Gema Wahyudewantoro; Yuli Andriani; Heti Herawati; Naomi Masnida Yunisia Siregar (ZOO INDONESIA, 2020)
Cipanas River is one river in West Java where its upstream region in Tampomas Mountain, Sumedang and it is emptied into the Java Sea, Indramayu. The study was aimed to investigate fish diversity in the downstream area of Cipanas River. The study was conducted by survey methods with census data collection techniques, taken place at 3 stations of Santing, Tempalong, and Cemara of Indramayu Regency. The parameters measured consisted water quality and fish assemblages. Water quality was measured referring to standard laboratory protocol, and fish collection was made by case net with different mesh sizes. The results showed that water quality conditions of the Cipanas River downstream was suitable for inhabiting fishes. There were as many as 548 individual fishes caught belonging to 21 species, 16 genera, and 14 families. Fish diversity was categorized as medium with 1.6 ≤ H ’≤ 2.2 indicating fairly good community structure, and the Evenness index was 0.81 ≤ E ≤ 0.86 to show highly evenly distributed.